FACTORS OF ENTERPRISE DEVELOPMENT IN CHINA - А.Е., Сериккaлиевa; А.Б., Абaгaнов (Journal of Oriental Studies, 2019)
China is a country with an ancient civilization. After the start of the policy of reform and openness in 1978, the PRC joined the advanced nations of the world. Today, China is the second economy in the world. This article analyzes the position of China in the global economy, discusses the key factors that determine the country’s economy. In addition, an analysis is made of the reasons that influenced the dynamic growth and the scientific discourse is cited as part of the statement that by 2030 China will become the largest economy in the world. Key words: business, factor, economy, technology, imbalance, reform, revaluation, external imbal- ance.